The functionalization of a cascade of C(sp2)–H/C(sp3)–H bonds: synthesis of fused dihydropyrazoles via visible-light photoredox catalysis. Issue 80 (7th September 2016) - Cheng, Jian; Xu, Pan; Li, Weipeng; Cheng, Yixiang; Zhu, Chengjian
Abstract : The functionalization of a cascade of C(sp 2 )–H/C(sp 3 )–H bonds in aldehyde hydrazones with simple 2, 2-dibromo-1, 3-dicarbonyls was achieved via visible-light photoredox catalysis. Abstract : The functionalization of a cascade of C(sp 2 )–H/C(sp 3 )–H bonds in aldehyde hydrazones with simple 2, 2-dibromo-1, 3-dicarbonyls was achieved via visible-light photoredox catalysis. This method, which involves free radical addition, polar crossover and 6π electrocyclic reaction, provides an efficient approach for the synthesis of complex fused dihydropyrazoles and related derivatives with moderate to good yields and excellent regioselectivity under mild reaction conditions.